Contrast Sensitivity Testing in Functional Ptosis and Dermatochalasis Surgery. Issue 4 (July 2015) - Fowler, Brian T.; Pegram, Trey A.; Cutler-Peck, Carolee; Kosko, Mark; Tran, Quynh T.; Fleming, James C.; Oester, Alan E.
Abstract : Purpose: To assess whether taped versus untaped contrast sensitivity testing reliably predicts improvement following eyelid-lifting surgery in patients with ptosis and/or dermatochalasis. Methods: This prospective study compared pre- and postoperative near contrast sensitivity in patients presenting to 2 ophthalmic plastic surgery practices with functional dermatochalasis and/or ptosis as determined by Humphrey visual field testing. Contrast sensitivity was measured using Mars near cards, held at 40 cm under standard lighting conditions. Logarithmic contrast sensitivity scoring cards were used for analysis. Marginal reflex distance was also collected. Pairwise comparison was used to assess the preoperative and postoperative contrast sensitivity scores. This study was conducted under the approval of the institutional review board. Results: Seventy-eight eyes of 41 patients with ptosis +/ dermatochalasis underwent eyelid-lifting surgery. The mean preoperative untaped contrast sensitivity was 1.30. The mean preoperative taped and postoperative log contrast sensitivities were 1.52 (11.85% increase) and 1.51 (11.44% increase), respectively. The difference between the 2 groups was not statistically significant ( p = 0.864). The marginal reflex distance improved by a mean of 2.0 ( p < 0.0005). Conclusions: Contrast sensitivity improves significantly following blepharoplasty and ptosis surgery. The degree of improvement in contrast sensitivity can accurately be predicted by preoperative taped/untaped testing. Contrast sensitivity testing may provide an additional screening modality for functional dermatochalasis and ptosis. In the future, contrast sensitivity may provide an additional preoperative assessment tool in patients who do not meet traditional visual field screening standards or who are unable to perform classic visual field testing. Abstract : The degree of improvement in contrast sensitivity following eyelid-lifting surgery can accurately be predicted by preoperative taped and untaped testing in patients with ptosis and/or dermatochalasis.